Central Government Political Intervention in the Implementation of Educational Autonomy in Indonesia - Lubis, Sopian; Sirozi, Muhammad; Sumanti, Solihah Titin (EDUTEC : Journal of Education And Technology, 2024)
This study critically examines the political intervention of the central government in Indonesia’s educational autonomy, focusing on the frequent changes in the national curriculum. Education, seen as a fundamental asset in fostering national potential, should be developed in a decentralized manner, allowing educational institutions the freedom to adapt to modern demands. However, the Indonesian government's use of the National Education System Law as a political tool has resulted in centralized policy enforcement, particularly in curriculum design, which often disregards regional needs. This research employs a qualitative approach, utilizing document analysis of legislative texts, historical records, and government policies to investigate the political influence on curriculum changes from 1947 to 2022. The findings show that the curriculum has been revised 11 times under political pressure, with both positive and negative outcomes. On the positive side, the curriculum updates ensure that students receive contemporary knowledge, but on the negative side, the frequent changes have caused confusion among teachers, negatively impacting student performance. This study highlights the complexity of political intervention in education and its implications for teaching and learning in Indonesia.